Selenium‐Doped Cathodes for Lithium–Organosulfur Batteries with Greatly Improved Volumetric Capacity and Coulombic Efficiency. Issue 33 (10th July 2017) - Zhou, Jinqiu; Qian, Tao; Xu, Na; Wang, Mengfan; Ni, Xuyan; Liu, Xuejun; Shen, Xiaowei; Yan, Chenglin
Abstract : For the first time a new strategy is reported to improve the volumetric capacity and Coulombic efficiency by selenium doping for lithium–organosulfur batteries. Selenium‐doped cathodes with four sulfur atoms and one selenium atom (as the doped heteroatom) in the confined structure are designed and synthesized; this structure exhibits greatly improved volumetric/areal capacities, and a Coulombic efficiency of almost 100% for highly stable lithium–organosulfur batteries. The doping of Se significantly enhances the electronic conductivity of battery electrodes by a factor of 6.2 compared to pure sulfur electrodes, and completely restricts the production of long‐chain lithium polysulfides. This allows achievement of a high gravimetric capacity of 700 mAh g −1 close to its theoretical mass capacity, an exceptional volumetric capacity of 2457 mAh cm −3, and excellent capacity retention of 92% after 400 cycles. Shuttle effect is efficiently weakened since no long‐chain polysulfides are detected from in situ UV/vis results throughout the entire cycling process arising from selenium doping, which is theoretically confirmed by density functional theory calculations. Abstract : A new type of selenium‐doped organosulfur polymer cathode with four sulfur atoms and one selenium atom (as the doped heteroatom) in the confined structure is designed and synthesized. The resulting Se‐doped electrodes exhibit greatly improved volumetric capacities and a Coulombic efficiency of almost 100% for highly stable lithium–organosulfur batteries.